Post-infectious sensory neuropathy with anti-GT1a and GQ1b antibodies associated with cold urticaria. (October 2018) - Zucchi, Elisabetta; Cavallieri, Francesco; Giovannini, Giada; Antonelli, Francesca; Mascia, Maria Teresa; Bedin, Roberta; Mandrioli, Jessica
Highlights: Cold-induced urticaria is a variety of urticaria induced by exposure to cold object. We describe a patient who developed post-infectious sensory neuropathy and cold urticaria. Anti-ganglioside antibodies search in serum was positive for anti-GQ1b and anti-GT1a IgG. This is the first report of an association between a sensory neuropathy and cold urticaria. Abstract: A 64 years-old woman presented subacute onset distal paraesthesia concurrently with cold-induced urticaria, a rare form of physical urticaria. Both the disturbances developed a fortnight after an upper respiratory tract infection. EMG confirmed an exclusively sensory polyneuropathy, with prolongation of distal latencies and reduction of amplitudes. Anti-GQ1b and anti-GT1a antigangliosides antibodies were found in serum. The clinical workout included CSF analysis, cryoglobulin and paraprotein search, neurotropic infective agents, neoplastic markers and extensive autoimmune disease antibodies analysis, all of which resulted negative. Intravenous immunoglobulins were administered, leading to progressive resolution of the sensory disturbance, while a combination of steroid and anti-histaminics treatment was used for the urticaria. The positivity for anti-ganglioside search with an EMG pattern characterized by a mixture of demyelinating and axonal features may suggest a nodo-paranodopathy at early stages. This is the first case of an association between an acute sensory neuropathy and cold urticaria, two immune mediated conditions apparently due to very different hypersensitivity pathways. A proposed mechanism for the co-occurence of these two conditions is presented, whereas this case expands the clinical spectrum of autoimmune diseases associated with anti-GQ1b and anti-GT1a antibodies.